The Impact of Abandonment On Deriving Legal Rulings and Jurisprudential Appliatcions Thereof: Applied Study (Raparin Journal of Humanities (RJH), 2025)
The chapters of the fundamentals of Islamic jurisprudence are close and intertwined with each other, including the abandonment of the Messenger, may God’s prayers and peace be upon him, with others.= Leaving the Messenger - may God bless him and grant him peace - an important legislative aspect that the mujtahid must know, because the ruling stops in many issues of calamities, heresies, and interests sent upon him, because some of the abandonment indicates permissibility, and some of them indicate prohibition and heresy, and some of them indicate hatred When the Messenger - may God’s prayers and peace be upon him - left, he did not do - may God’s prayers and peace be upon him - what was destined for him in the universe, so he helps to differentiate between heresy and the sent interest.= The Messenger - may God’s prayers and peace be upon him - is the legislator by means, so his leaving the legislative had an impact on deriving legal rulings, and he did not fulfill his conditions by being one of the acts of worship and that the requisite is present and the impediment is negated, like his leaving the prayer on the martyr.= The Messenger (may God’s prayers and peace be upon him) did not deliberately omit any of the actions and words except that they are related to the door of the legitimate purposes of the purpose of facilitating the Islamic nation, preserving the soul, warding off corruption and bringing interest and other purposes.= Acting by leaving is closing what the Messenger - may God bless him and grant him peace - did not do - and this means that adherence to leaving is a leader in closing the door of innovation in religion, because from leaving is evidence of prohibition, recommendation and permissibility, and not all of them are in one position, so work is the opposite of what the Messenger left ( Peace be upon him) may lead to a great spoiler, which is creating innovations, so they must be blocked.= The abandonment of the Messenger - may God’s prayers and peace be upon him - is either due to the call of the human nature, or there is evidence of his specialization in it, or a clarification and confirmation of the entirety of the Qur’an and a well-known ruling, such as the abandonment of the Messenger - may God’s prayers and peace be upon him - praying for the hypocrites and standing over their graves in compliance with the Almighty’s saying: {And do not pray One of them dies, never, and do not stand over his grave} (At-Tawbah: 84), and this means that abandonment has a great impact in extracting the jurisprudential ruling - as a second source for deriving rulings - and from other legal evidence or from the Turk itself only without other evidence, and this means when There was no evidence other than the Turk, and this second is the purpose of the message in particular.= The Turk is one of the sources for deriving jurisprudential rulings, and there are various jurisprudential applications attesting to this.